Climate fluctuation impacts in Astronium urundeuva (M. Allemão) Engl. silvicultural characters in the Brazilian Cerrado - Corrêa, Aparecida Juliana Martins; Alves, Patrícia Ferreira [UNESP]; Cambuim, José [UNESP]; Moraes, Mario Luiz Teixeira de [UNESP]; Freitas, Miguel Luiz Menezes (IOP Publishing, 2022)
Currently, mankind is responsible for changing our planet’s conditions. These changes are usually catastrophic, and yet, mankind does not develop preventative strategies to reduce their impacts. However, a species present in the Brazilian Cerrado, Astronium urundeuva, can be very economically logged and has a known landscape distribution, but lacks information regarding the impacts of climate change on its silviculture. This research aimed to verify A. urundeuva’s silvicultural behavior under current environmental conditions. Progenies from three populations (Cerrado and Atlantic Forest/Cerrado transition) were measured for silvicultural characters: height (HT) and diameter at breast height (DBH), in 2019. Climatic data (temperature, precipitation, evapotranspiration and soil available water, averages and accumulated) were also measured between 1996 and 2018. Descriptive and sequential water balance analysis, descriptive statistics, collinearity tests and a multiple linear regression were performed. There was water deficit in all years (−12.7 mm) researched, which showed an irregular rainfall distribution in Selvíria-MS, concentrated mostly in summer. Average HT ranged from 8.02 m to 10.69 m, while average DBH ranged from 0.10 m to 0.12 m, with high variability (CVs between 21.99% and 34.77%). There was significant correlation between HT, DBH, T m , E t o m and Et o a and between Et o m , Et o a and H 2 O d , which highlighted the importance of water availability . Multiple linear regression showed E t o m has a direct and negative relationship with silvicultural characters, implying productivity losses while evapotranspiration increases. Even though it is not a typical Cerrado species, A. urundeuva may have adapted to phytogeographic domain conditions, with slow growth due to water deficit for its survival, considering that, in Brazil, climate change has resulted from annual variations.
Keywords: evapotranspiration; forest productivity; germplasm; selection; water stress